Risk factors of neurologic deficit after thoracolumbar burst fracture - Liu, Yuxi; Zhang, Shilin; Feng, Daxiong; Luo, Jing; Zhang, Hong; Wang, Likun (Frontiers in Neurology, 2025)
IntroductionTraumatic fractures of the vertebral bodies in the thoracolumbar region are the most common type of spinal fractures. Some studies suggest that neurological deficits associated with these fractures may be linked to spinal canal compromise, kyphosis angle, and other factors. However, this relationship remains controversial. The present study aimed to identify the risk factors for neurologic deficits following thoracolumbar burst fractures (TBF).MethodsThis study included 322 patients with TBF, comprising 115 patients with lamina fractures (LF) and 207 patients without lamina fractures (NLF). Neurological deficits were classified according to the American Spinal Injury Association (ASIA) classification, with 75 patients exhibiting neurological deficits and 247 patients without deficits. Clinical data, ASIA classification, and imaging findings were analyzed and compared between the two groups. Risk factors were assessed using logistic regression.ResultsCompared with the NLF group, the LF group had higher ASIA classification scores (P < 0.05). Multivariate logistic regression identified laminar fracture (OR: 0.019, 95% CI: 0.005–0.070, P < 0.000), car accident (OR: 6.082, 95% CI: 1.248–29.636, P = 0.025), and falling accident (OR: 8.429, 95% CI: 2.143–33.153, P = 0.002) as independent variables associated with neurologic deficit. Additionally, the ROC curve revealed that laminar fractures and falling accidents had a high risk association value. A risk association equation, Logit (P) = −4.358 + 3.535 × laminar fracture – 1.353 × falling accidents, was established based on the high-value indicators.ConclusionLaminar fractures, car accidents, and falls were identified as independent risk factors for neurological deficits following TBF. Additionally, laminar fractures and falls demonstrated a high risk association value. These findings provide valuable insights for optimizing rehabilitation strategies and guiding surgical decision-making.